(untitled) (Development Service Industry Management, 2024)
The aim of the research is to identify the factors shaping the quality of the restaurant business in today’s realities, assess quality using highlighted factors, and determine disparities or synergies in the assessment of restaurant business quality from the perspectives of both consumers and restaurateurs. Our objective is to compile a list of factors influencing the quality of the establishment and determine the results of compliance/non-compliance with the proper quality of each factor on the establishment’s operations and its consumers, as well as determine the significance of these factors through a questionnaire survey. Design/methodology/approach. To address the objectives outlined in the work, various general scientific and specialized research methods are employed. A systematic approach to reviewing literature sources has allowed the identification of a set of factors influencing the quality of the restaurant business. The abstract and logical method is utilized for theoretical generalizations, defining key categories and concepts, as well as for forming research conclusions. Analysis and synthesis methods are employed to compile a list of key factors in assessing the quality of the restaurant business. Findings – The method of expert assessment remains one of the effective methods for determining the level of quality based on specified parameters that constitute dominant factors influencing the quality of services in the restaurant business. Based on identified factors such as hospitality economics, menu, cleanliness and safety, interior and ambiance, innovations, internet technologies, loyalty programs; the role of the head chef, social responsibility, infrastructure, and pricing policy; marketing and advertising, it is proposed to conduct an analysis and identify discrepancies between the consumer’s and restaurateur’s perception of service quality. Originality/value – This study highlights the similarities and differences in approach to definition of the level of service quality in the restaurant business. The main factors have been considered, and it is proposed that when assessing the quality of services, a bilateral determination of the significance of these factors be conducted for both consumers of these services and restaurateurs. In further research and efforts to improve the quality of restaurant services, this will enable prioritizing the enhancement of service quality factors for restaurateurs. Practical implications – The materials presented in the article will be useful for employees responsible for the quality of services in the restaurant business.